The relationship between depression stigma and depression literacy on psychological help seeking attitudes among university students - Ikram, Nur Dhaniah Zainul; Yusop, Yusni Mohamad; Zainudin, Zaida Nor; Wan Othman, Wan Norhayati; Puad Mohd Kari, Dharatun Nissa (Human Resources Management Academic Research Society (HRMARS), 2024)
The aim of this study is to investigate the relationship and influence of individual’s depression stigma and depression literacy on attitude of seeking counselling help among youth namely university students. The respondents of this study are 302 students from public universities in Malaysia namely Universiti Sains Islam Malaysia (USIM). This is a correlational study to identify the relationship and influence between variables. Data collected from the sample will be analysed using Statistical Package for Social Sciences (SPSS) version 23. Statistical analysis that will be used are descriptive and inferential analysis. Findings of the study shows that the relationship between depression stigma and psychological help seeking behaviour indicates a strong negative relationship. The relationship between depression literacy and psychological help seeking behaviour indicates a weak positive relationship. The gender difference in relation to depression stigma shows male have significantly higher negative stigma rather than female. The gender difference in relation to depression literacy demonstrate that male have significantly lower literacy on depression rather than female. The gender difference in relation to psychological help seeking behaviour shows that male have significantly lower tendency on psychological help seeking attitudes rather than female.